2013
DOI: 10.1021/sc400271k
|View full text |Cite
|
Sign up to set email alerts
|

Novel Epoxy Coating Based on DMSO as a Green Solvent, Reducing Drastically the Volatile Organic Compound Content and Using Conducting Polymers As a Nontoxic Anticorrosive Pigment

Abstract: This work reports novel anticorrosive epoxy coatings based on safer dimethyl sulfoxide solvent and free of zinc anticorrosive pigment. The latter was replaced by conducting polymers, as nontoxic anticorrosive pigments. The procedure used for their formulation, spectroscopic characterization, thermal and mechanical properties have been discussed and compared with those of conventional epoxy coatings. Furthermore, accelerated and longterm corrosion assays have evidenced that the new epoxy coatings protect steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The effect of the addition of P3TMA (1%) in the paint formulation was also noticed by pull-off test (Figure 10). The tensile strength obtained for samples in dry state is much higher than the sample with 3V nanocoating, corroborating to the idea that conducting polymers also can actuate as adhesion promoters [26][27][28][29][30]. However, this effect was lost over time in the wet samples, where the adhesion reduction was almost the same than panels coated with 3V/epoxy bilayer system (15% and 16.7%, respectively).…”
Section: Adhesion Measurementssupporting
confidence: 75%
See 1 more Smart Citation
“…The effect of the addition of P3TMA (1%) in the paint formulation was also noticed by pull-off test (Figure 10). The tensile strength obtained for samples in dry state is much higher than the sample with 3V nanocoating, corroborating to the idea that conducting polymers also can actuate as adhesion promoters [26][27][28][29][30]. However, this effect was lost over time in the wet samples, where the adhesion reduction was almost the same than panels coated with 3V/epoxy bilayer system (15% and 16.7%, respectively).…”
Section: Adhesion Measurementssupporting
confidence: 75%
“…In order to improve the previous results with AA2024 alloy, two further approaches were investigated: (i) the incorporation of EDTPO to the VTMS/TEOS sol-gel formulation and (ii) the incorporation of a conducting polymer to the epoxy paint. Since the advantage combination of the use of conducting polymers (CPs), as anticorrosive additive, with organic coatings has granted the improvement of corrosion protection of metals [26][27][28][29][30], accordingly, we incorporated a soluble semiconducting polythiophene derivative (P3TMA) to the epoxy paint formulation in order to evaluate its influence to the adhesion between the sol-gel inner nanocoating and the epoxy outer coating.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of drying activity of Bz 1 Fc was performed on solvent‐borne alkyd resin modified with soybean oil S471, which is widely used in industry as a binder for economic primers and anticorrosive coatings. Weak solubility of Bz 1 Fc in formulation was overcame by predissolution of the drier in DMSO, which seems to be a promising candidate to replace toxic volatile solvents . In order to optimize dosage of the drier, mechanical properties of test coatings were examined in a range of metal concentrations 0.01–0.1 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…This observation offers interesting perspectives as Please do not adjust margins Please do not adjust margins DMSO is typically considered to be a green solvent. [42][43][44] These results revealed that the role of the solvent is complex and cannot be simply described in terms of polar vs. nonpolar or protic vs. aprotic properties. At first glance, one could conclude that the polarity of the solvent would explain Mlac vs. ttMA reaction pathways, but if that were the case Scheme 6.…”
Section: Isomerization To Ttma In Polar Aprotic Solventsmentioning
confidence: 98%